Direct conversion of CO and H2O into liquid fuels under mild conditions - Yao Xu (Nature Portfolio, 2019)
Developing new carbon resource transformation protocols leading to the production of liquid fuels with high selectivity under mild conditions remains challenging. Here the authors present a novel and energy-efficient catalytic route to directly transform CO and H2O to liquid fuels at low temperature in aqueous phase.